Tick-Borne Illnesses. Issue 2 (March 2016) - Choi, Edwin; Pyzocha, Natasha J.; Maurer, Douglas M.
Abstract : Tick-borne diseases are prevalent throughout the United States. These illnesses are caused by a variety of different pathogens that use ticks as vectors, including bacteria, viruses, rickettsia, and protozoa. Some of the most common illnesses caused by ticks are Lyme disease, Rocky Mountain spotted fever, babesiosis, ehrlichiosis, anaplasmosis, tularemia, Colorado tick fever, tick-borne relapsing fever, and Powassan disease. Unique skin changes, fever, and influenza-like symptoms may indicate tick-borne disease. Early diagnosis can be difficult as well as nonspecific and can resemble overtraining syndrome. Diagnosis is important to facilitate early treatment to decrease morbidity and mortality and should often be initiated before a definitive diagnosis is made. Treatment guidelines are published by the Centers for Disease Control and Prevention. As tick-borne diseases increase and their geographic regions expand, it is important for providers to distinguish the often overlapping and diverse presentations of these diseases.